Analysis on the Privacy of DID Service Properties in the DID Document - Kim, Kyung Hoon; Lim, Seungjoo; Hwang, Dong Yeop; Kim, Ki Hyung (International Conference on Information Networking, 2021)
Decentralized Identifiers (DIDs) are a technology that allows individuals to realize self-sovereign identity. The advantage of the DIDs is that individuals can decide what information to disclose and transparently review the details of the disclosed information. In the core architecture of DIDs, a DID document associated with a DID is derived, and this document is open to the public to access. However, DID service properties in the DID document raises a dataveillance problem. In this paper, we analyze the risks of leaking sensitive information that may be included in the DID authentication process through a scenario.
Keywords: Sensitive informations; Service properties; Blockchain; Decentralized Identifiers; Privacy Protection; Self-Sovereign identity